On Double Statistical P-Convergence of Fuzzy Numbers - Ekrem Savaş; Richard F. Patterson (Journal of Inequalities and Applications, 2009)
Savas and Mursaleen defined the notions of statistically convergent and statistically Cauchy for double sequences of fuzzy numbers. In this paper, we continue the study of statistical convergence by proving some theorems.